Meninas na medida socioeducativa de internação: vozes do Estado sobre a juventude feminina negra e periférica - Grillo, Nathalí Estevez (2024)
This work aims to find out what the State enunciates about a section of Brazilian black feminine peripheral youth: the female adolescents who are serving a socio-educational detention order. We have selected two technical managers from two feminine socioeducational facilities of Fundação CASA, located in the capital of the state of São Paulo as representatives of the State. Both of them have a degree in Psychology. One interview of each manager extracted from another research intitled Análise da execução das medidassocioeducativas de meninas adolescentesemprivação de liberdade (IBAM, 2021) was considered. These interviews took place between July and august of 2019 and were carried out by us. The starting points of this investigation were Feminist Epistemologies and concepts such as i) situated knowledge; 11) intersectionality; iii) penal abolitionism; iv) antiunderageism to reflect the content of the interviews. The methodology that inspired it was HistóriaVivente [Living History]. The reflections were divided into three axes: i) institutional racism; ii) consequences of the detention order on account of being a girl and iii) politics of affection and expressions of sexuality. We argue that it is not possible to assure the integral protection of teenagers concomitantly with the existence of spaces of deprivation of liberty